Metabotropic glutamate receptors mediate excitatory transmission in the nucleus of the solitary tract - Glaum, SR (J Neurosci, 1992)
Following microinjection into the nucleus tractus solitarius (NTS), the effects of glutamate on the baroreceptor reflex are poorly antagonized by kynurenic acid and DL-2-amino-5-phosphonovaleric acid, suggesting the possible involvement of metabotropic glutamate receptors in this response. The metabotropic glutamate receptor agonist 1S,3R-1- aminocyclopentane-1,3-dicarboxylic acid (1S,3R-ACPD) depolarized neurons located medial to the tractus solitarius (TS) at the level of the area postrema in coronal sections of the rat NTS. This effect was mimicked by glutamate and was not blocked by antagonists at alpha-amino- 3-hydroxy-5-methyl-isoxazole-4-propionic acid (AMPA)/kainate or NMDA receptors. 1S,3R-ACPD also produced an inward current under voltage clamp that was not accompanied by a rise in [Ca2+]i, monitored with the Ca(2+)-sensitive dye fura-2. Conversely, the muscarinic agonist carbachol produced an outward current and a rise in [Ca2+]i. 1S,3R-ACPD reduced both the excitatory and the inhibitory postsynaptic current resulting from single electrical stimuli in the region of the TS. High- frequency stimulation of the TS produced an inward current in the presence of AMPA/kainate and NMDA receptor blockers. This current had similar properties to that produced by 1S,3R-ACPD. Thus, metabotropic glutamate receptors may mediate a component of excitatory transmission in the NTS.